Targeting MCL‐1 and BCL‐2 with polatuzumab vedotin and venetoclax overcomes treatment resistance in R/R non‐Hodgkin lymphoma: Results from preclinical models and a Phase Ib study. Issue 3 (17th January 2023) - Lasater, Elisabeth A.; Amin, Dhara N.; Bannerji, Rajat; Mali, Raghuveer Singh; Barrett, Kathy; Rys, Ryan N.; Oeh, Jason; Lin, Eva; Sterne‐Weiler, Tim; Ingalla, Ellen Rei; Go, MaryAnn; Yu, Shang‐Fan; et al.
Abstract: The treatment of patients with relapsed or refractory lymphoid neoplasms represents a significant clinical challenge. Here, we identify the pro‐survival BCL‐2 protein family member MCL‐1 as a resistance factor for the BCL‐2 inhibitor venetoclax in non‐Hodgkin lymphoma (NHL) cell lines and primary NHL samples. Mechanistically, we show that the antibody‐drug conjugate polatuzumab vedotin promotes MCL‐1 degradation via the ubiquitin/proteasome system. This targeted MCL‐1 antagonism, when combined with venetoclax and the anti‐CD20 antibodies obinutuzumab or rituximab, results in tumor regressions in preclinical NHL models, which are sustained even off‐treatment. In a Phase Ib clinical trial (NCT02611323) of heavily pre‐treated patients with relapsed or refractory NHL, 25/33 (76%) patients with follicular lymphoma and 5/17 (29%) patients with diffuse large B‐cell lymphoma achieved complete or partial responses with an acceptable safety profile when treated with the recommended Phase II dose of polatuzumab vedotin in combination with venetoclax and an anti‐CD20 antibody.